PENGEMBANGAN MODUL AJAR BERBASIS PENDIDIDKAN MATEMATIKA REALISTIK PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL KELAS X SMA NEGERI 2 BOAWAE - Priska Ermelinda Noa; Melkhior Wewe (Jurnal Ilmiah Mandalika Education (MADU), 2024)
This research aims to develop a teaching module for a two variable linear equation system based on realistic mathematics education model for class X high school students. This research aims to produce a prodact in the from of a two variable linear equation system learning module based on a realistc mahematics education model using the EDDIE model, namely analysis, design,development,implementation, and evaluation.the instrument used in this research were expert eqistionaire sheets to measure the validity of teaching materials, teacher response questionaires and student response questionaires and student student response questinaires to measure the practicaly of questionaire trials student nad teacher respondets regarding the modules or products development obtained result with good criteria.based on the results of the assesment by student, namely 3,64 which is in good criteria and the rselts with good criteria. Based on the result of the asessment by teacher respondent namely, 3,8 which is in good criteria, so that the product developed is suitable fo use.